CCAFS Theme 1 Workshop: Feedback - Peter Crawford - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
From 6 to 8 December, CCAFS theme 1 organized a workshop staged on the Addis Ababa campus of the International Livestock Research Institute (ILRI). The workshop titled 'Developing climate-smart crops for 2030 world' involved over 40 participants from 16 countries, broadly divided along either side of the breeding / modeling continuum. (See: https://ccafs.cgiar.org/blog/mitigating-change-climate-relations-breeders-and-modelers-africa-unite-climate-smart-crops)